PERUMUSAN STRATEGI PEMASARAN BERKELANJUTAN THE BLOOMS GARDEN UNTUK MENDUKUNG KOLABORASI DESTINASI PARIWISATA - Gde Indra Bhaskara; Nararya Narottama; -, Ni Wayan Wulaningsih (Jurnal Belantara, 2024)
This research was carried out at the tourist destination The Blooms Garden Bedugul Bali. This study aims to analyze (1) the current marketing strategy of The Blooms Garden Bedugul Bali; and (2) formulation of a sustainable marketing strategy for The Blooms Garden to support collaborative tourism destinations in Bedugul. This research is categorized as research with a Concurrent Mixed Method approach. The data collected is in the form of qualitative data and quantitative data. Qualitative data were collected from interviews, observations and documentation. Meanwhile, quantitative data was collected by gathering information from The Blooms Garden management regarding strengths, weaknesses, opportunities and threats which were then converted into numerical data with weights and ratings. Analysis of data sourced from interviews, observation and documentation was analyzed using interactive data analysis techniques from Miles & Huberman. Determination of the marketing strategy implemented by the manager of the tourist attraction of The Blooms Garden is analyzed using SWOT analysis. The results of the study show that (1) the current marketing strategy undertaken by The Blooms Garden Bedugul Bali to attract and increase tourist visits includes the installation of banners and billboards scattered along the road from Denpasar to Bedugul; website opening; via social media; and cooperate with online travel agencies such as traveloka, tiket.com, and so on. However, the marketing strategy undertaken by The Blooms Garden has not succeeded in bringing in tourists as expected; and (2) The Blooms Garden's sustainable marketing strategy formulation to support collaborative tourism destinations in the Bedugul region is an integrated diversification strategy. This marketing strategy means that The Blooms Garden Bedugul Bali can integrate with other tourism destinations in the Bedugul area. The sustainable marketing strategy in collaboration with other destinations in the Bedugul area is intended as an effort to increase tourist visits, especially environmentally conscious tourists who often visit the well-known Botanical Gardens and Lake Beratan, directed to visit The Blooms Garden as well. If possible, pass tickets apply between the Botanical Gardens, Lake Beratan and The Blooms Garden.